Data of range of thoracic kyphosis and lumbar lordosis between line and staff personnel of armed forces in Kermanshah, Iran - Mohammad Bagher Shamsi; Korosh Veisi; Luckman Karimi; Ameneh Safari (Data in Brief, 2022)
Two hundred people of the line (new and experienced) and staff (new and experienced) armed forces consisted of the samples. Using a flexible ruler, spinal curves (thoracic kyphosis and lumbar lordosis) were measured. The biggest kyphosis and lordosis values were seen in experienced staff and experienced line groups and the smallest kyphosis and lordosis values were seen in new staff and experienced staff groups, respectively. One-way repeated-measures analysis of variance (ANOVA) was carried out on the thoracic kyphosis and lumbar lordosis measures of the line and the staff groups to assess differences between groups and the post hoc test was carried out to define the group that was significantly distinct from the others.